The Oxford companion to American military history - Chambers, John Whiteclay; Anderson, Fred, 1949- (Oxford University Press, 1999)
Entries cover marjor wars, battles, military leaders, branches of service, weapons, naval vessels, aircraft, types of warfare, military life, Acts of Congress, peace groups, and cultural influences.